2014
DOI: 10.1016/j.apunts.2013.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between aerobic and anaerobic power, and Special Judo Fitness Test (SJFT) in elite Iranian male judokas

Abstract: Introduction: The purpose of this study was to assess the relationship between aerobic and anaerobic power, and special judo fitness test in elite male judokas. Method: Nineteen elite Judokas [age 24.3 (3.1) yr, height 1.78 (.06) m, body mass 76.4 (11.2) kg, body mass index 20.2 (3.6) kg·m −2 and body fat 11.0 (1.8)%] performed a graded exercise test in treadmill, the Wingate anaerobic test for arms and the special judo fitness test. The graded exercise test in treadmill estimated maximal oxygen uptake (VO 2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 8 publications
0
15
0
1
Order By: Relevance
“…Una prueba de campo ampliamente utilizada con atletas de judo es el Special Judo Fitness Test (SJFT) 5 , con la cual se han reportado diferencias entre atletas de diferente nivel competitivo 6 , y su relación con el rendimiento aeróbico y anaeróbico 7 . Debido a las características comunes entre lucha olímpica y judo, el SJFT recientemente ha sido adaptado a lucha olímpica con el nombre de Special Wrestling Fitness Test (SWFT) 8-10 , reportándose su relación con el rendimiento aeróbico medido de forma indirecta 9,10 .…”
Section: Introductionunclassified
“…Una prueba de campo ampliamente utilizada con atletas de judo es el Special Judo Fitness Test (SJFT) 5 , con la cual se han reportado diferencias entre atletas de diferente nivel competitivo 6 , y su relación con el rendimiento aeróbico y anaeróbico 7 . Debido a las características comunes entre lucha olímpica y judo, el SJFT recientemente ha sido adaptado a lucha olímpica con el nombre de Special Wrestling Fitness Test (SWFT) 8-10 , reportándose su relación con el rendimiento aeróbico medido de forma indirecta 9,10 .…”
Section: Introductionunclassified
“…These finding have usually been attributed to the fact that elite athletes have a higher volume of judo-specific training (Drid et al, 2015) and, consequently, are able to perform better on specific motor tasks like number of throws (Franchini et al, 2005;Sterkowicz-Przybycie n et al, 2019). The HR measures after the test indirectly estimated the athlete's aerobic fitness (Hesari et al, 2014), but due to its high variability, it may not be a good marker to discriminate groups.…”
Section: Discussionmentioning
confidence: 99%
“…Each partner should be positioned six meters apart, and the executant should run to each partner to throw him/her as many times as possible. The SJFT indirectly estimates the athletes' aerobic capacity (heart rate after the test) and anaerobic capacity (number of throws) (Hesari et al, 2014;Sterkowicz & Franchini, 2001), and it has been reported to be predominantly anaerobic, although there have been higher values of oxygen uptake during the test (Franchini et al, 2011). In addition, this test has distinguished between athletes of different competitive levels (Franchini et al, 1998;Katralli & Goudar, 2012) and weight categories (Sterkowicz & Franchini, 2001), and it has detected changes in physical performance after a periodized training program (Marques et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies were performed on athletes competing at the national level and during the transition period (one–two weeks after the respective main competitions) [ 18 ]. Moreover, previous research shows that the result of judo fight is significantly correlated with the level of judo special skills [ 19 , 20 ]. Those skills are determined by the level of aerobic capacity in the cadet age group [ 21 ].…”
Section: Introductionmentioning
confidence: 99%